Developing English Materials on Listening and Speaking for Survival English Program Students of Rafa’s English House Gumukmas - Ika Atiqotul Maula; Ika Desy Wardani; Aminullah Aminullah (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2017)
This study employed Educational Research and Development (RnD). The employment was purposed to embody the appropriate instructional materials in form of textbook that focused on listening and speaking for Survival English (SE) program students at LKP Rafa’s English House (ROSE), Gumukmas. The research product named Fun Listening and Speaking 1 was designed based on the competence based syllabus of LKP ROSE, the finding data gathered through need analysis and Contextual Teaching Learning (CTL). Concerning to these, a set of procedures proposed by Borg and Gall are being applied in this study. The research instruments used to collect the data consisted of Course Syllabus, Focused Group Discussion (FGD), interview, questionnaires, and observation sheet and checklist validation forms. Expert validation was carried out to evaluate the textbook developed for the product betterment. Moreover, to know the applicability of the materials and students’ responses, the real tryout phase on some selected chapters during the research period had been conducted. For the reasons, the textbook on listening and speaking for SE program students is ready to be applied in teaching learning activity.